Epigenetic Modulation: A Promising Avenue to Advance Hematopoietic Stem Cell-Based Therapy for Severe Autoimmune Disorders - Timothy Hsiao, Hsin-hao (Epigenetic Diagnosis & Therapy (Discontinued), 2015)
Severe autoimmune disorders, such as certain serious forms of multiple sclerosis, rheumatoid arthritis, and systemic lupus erythematosus, lead to poor prognosis for patients and can be fatal. Traditional immunosuppression therapies are rarely curative but only temporarily relieve patients from the flares. Arising “epigenetic” medications may enhance specificity but limitations still exist for their applications to severe autoimmune disorders due to the medications targeting differentiated immune cells. Hematopoietic stem cell-based therapy represents a different therapeutic strategy, which aims to reconstitute the functionality of the whole immune system. Such a re-constitutive approach has demonstrated long-lasting clinical benefits. Currently, hematopoietic stem cell transplantation remains a challenging and risky procedure, but recent scientific discoveries indicate that targeting epigenetics in hematopoietic stem cells bears promise to improve both the success rate and safety profile of hematopoietic stem cell-based therapy for treating severe autoimmune disorders.
Keywords: hematopoietic stem cell